2020
DOI: 10.1152/ajprenal.00523.2019
|View full text |Cite
|
Sign up to set email alerts
|

Expression, localization, and functional properties of inwardly rectifying K+channels in the kidney

Abstract: Inwardly rectifying K+ (Kir) channels are expressed in multiple organs and cell types and play critical roles in cellular function. Most notably, Kir channels are major determinants of the resting membrane potential and K+ homeostasis. The renal outer medullary K+ channel (Kir1.1) was the first renal Kir channel identified and cloned in the kidney over two decades ago. Since then, several additional members, including classical and ATP-regulated Kir family classes, have been identified to be expressed in the k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 66 publications
(61 reference statements)
2
12
0
Order By: Relevance
“…A possible explanation for this is that depolarization in the principal cells of these mice stimulates intracellular signaling cascades that stimulate ENaC‐dependent K + secretion (Sorensen et al, 2019 ). This is similar to the concept that K ir 4.1/K ir 5.1 serves as a potassium sensor in the DCT to regulate Na + reabsorption through the sodium chloride cotransporter (Manis et al, 2020 ; Su et al, 2019 ) explaining hypokalemia observed in rodents and humans lacking functional K ir 4.1/K ir 5.1 channels (Celmina et al, 2019 ; Cuevas et al, 2017 ; Malik et al, 2018 ; Palygin, Levchenko, et al, 2017 ; Schlingmann et al, 2021 ; Su et al, 2019 ; Tomilin et al, 2018 ). Thus, the precise effects of changes in K ir 4.1/K ir 5.1 activity on K + homeostasis likely depend on the degree of change as well as the affected nephron segment.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…A possible explanation for this is that depolarization in the principal cells of these mice stimulates intracellular signaling cascades that stimulate ENaC‐dependent K + secretion (Sorensen et al, 2019 ). This is similar to the concept that K ir 4.1/K ir 5.1 serves as a potassium sensor in the DCT to regulate Na + reabsorption through the sodium chloride cotransporter (Manis et al, 2020 ; Su et al, 2019 ) explaining hypokalemia observed in rodents and humans lacking functional K ir 4.1/K ir 5.1 channels (Celmina et al, 2019 ; Cuevas et al, 2017 ; Malik et al, 2018 ; Palygin, Levchenko, et al, 2017 ; Schlingmann et al, 2021 ; Su et al, 2019 ; Tomilin et al, 2018 ). Thus, the precise effects of changes in K ir 4.1/K ir 5.1 activity on K + homeostasis likely depend on the degree of change as well as the affected nephron segment.…”
Section: Discussionsupporting
confidence: 67%
“…On the apical membrane, sodium reabsorption through ENaC generates a lumen‐negative transepithelial potential that also drives K + secretion through the ROMK (K ir 1.1) and the big conductance K + (BK) channels (Bailey et al, 2006 ; Wang & Giebisch, 2009 ; Welling, 2016 ). On the basolateral membrane, K + recycling occurs through the basolateral homo‐ and heteromeric K ir 4.1 and K ir 4.1/K ir 5.1 channels (Manis et al, 2020 ; Su et al, 2019 ). Recent preclinical studies have shown that the basolateral K ir 4.1/K ir 5.1 channel is critical for renal salt handling and blood pressure control (Cuevas et al, 2017 ; Palygin, Levchenko, et al, 2017 ; Palygin et al, 2017 ; Penton et al, 2020 ; Tomilin et al, 2018 ; Wang, Su, et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Decreased or increased activity of potassium channels caused by loss-of-function and gain-of-function (GOF) variants in the corresponding genes, respectively, underlies a broad spectrum of human disorders affecting the function of the central nervous system, heart, kidney, and other organs [ 5 8 ]. While the association of epilepsy and intellectual disability (ID) with variants affecting function in genes encoding potassium channels has been greatly appreciated [ 2 , 5 , 6 ], GOF missense variants in K + channel encoding genes in individuals with syndromic developmental disorders have only recently been recognized [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…SS Kcnj16-/rats also showed deficits in acute (CNS-respiratory) and chronic (renal) acid/base dysregulation (20). These findings suggest that Kir5.1 plays a non-redundant role in fundamental physiological homeostasis (18,19,(21)(22)(23). Given that Kir5.1 is highly expressed in the CNS, loss of Kir5.1 expression may destabilize the resting membrane potential, thereby altering neuronal excitability and resulting in additional neurological phenotypes.…”
Section: Introductionmentioning
confidence: 96%